Montage/mediation/publicity: Far from Vietnam. (11th March 2019) - Fresko, David
Abstract: Far from Vietnam (Chris Marker, et al., 1967), though heralded as a major contribution to the history of radical documentary and extolled as a cri de coeur about the inability of French intellectuals to sufficiently contribute to the anti-war struggle, has been inadequately understood for the internationalism underlining its politics and the montage employed to achieve it. Its production linked France, the USA, Cuba and Vietnam; its textual shape consolidated its transnational exchanges through montage, which marshalled multiple counter-cinematic techniques to link the real and imaginary addressees of global anti-war publics across cuts generative of new creative cartographies and political subjectivities. Far from Vietnam 's form signalled the counter-cinema that it was while simultaneously calling into the being the counter-public necessary to confront US militarism. As opposed to uncritical evocations of solidarity, which elide differences between home and abroad, the essay concludes by arguing that Far from Vietnam, much as its title suggests, realizes and questions international political praxis's stability as a category of thought and action.